PENGEMBANGAN MANAJEMEN SEKOLAH RAMAH ANAK DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS SISWA SEKOLAH DASAR - Harahap, Rizki Dwi Aprilia; Purba, Diva Egita; Siburian, Parasina Caroldion Br; Namira, R. Nazra Fitri; Budianto, Agum (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT The development of Child-Friendly Schools (CFS) is crucial in creating a safe, inclusive learning environment that supports the psychological development of elementary school students. However, the implementation of CFS in many schools still faces challenges, particularly in terms of management, teacher readiness, and the availability of supporting facilities. This study aims to analyze how school management develops CFS and how these efforts contribute to improving students’ psychological well-being. The study employs a qualitative approach using a case study method. Data were collected through observations, in-depth interviews with principals, teachers, and students, as well as analysis of school documents. The study includes identification of initial conditions and needs mapping, analysis of child protection policies and programs, evaluation of CFS implementation in classrooms and the school environment, and assessment of its impact on indicators of students’ psychological well-being. The results indicate that CFS development is carried out through the formulation of child protection policies, enhancement of teachers’ capacity in positive parenting, strengthening guidance and counseling services, and provision of child-friendly facilities such as counseling rooms and safe play areas. The findings also show increased student self-confidence, reduced learning anxiety, and improved academic motivation. Overall, the study concludes that school management that consistently applies CFS principles is able to create a safe and supportive learning environment, thereby significantly contributing to the improvement of students’ psychological well-being. ABSTRAK Pembangunan Sekolah Ramah Anak (SRA) sangat penting dalam menciptakan lingkungan belajar yang aman, inklusif, dan mendukung perkembangan psikologis siswa sekolah dasar. Namun, implementasi SRA di banyak sekolah masih menghadapi hambatan, terutama dalam hal manajemen, kesiapan guru, dan ketersediaan fasilitas pendukung. Penelitian ini bertujuan untuk menganalisis bagaimana manajemen sekolah mengembangkan SRA dan bagaimana upaya ini berkontribusi dalam meningkatkan kesejahteraan psikologis siswa. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus. Data dikumpulkan melalui observasi, wawancara mendalam dengan kepala sekolah, guru, dan siswa, serta analisis dokumen sekolah. Penelitian ini mencakup identifikasi kondisi awal dan pemetaan kebutuhan, analisis kebijakan dan program perlindungan anak, evaluasi implementasi CFS di kelas dan lingkungan sekolah, serta penilaian dampak terhadap indikator kesejahteraan psikologis siswa. Hasil penelitian menunjukkan bahwa pengembangan SRA dilakukan melalui formulasi kebijakan perlindungan anak, peningkatan kapasitas guru dalam parenting positif, penguatan layanan bimbingan dan konseling, serta penyediaan fasilitas ramah anak seperti ruang konseling dan area bermain aman. Temuan juga menunjukkan peningkatan kepercayaan diri siswa, penurunan kecemasan belajar, dan peningkatan motivasi akademik. Secara keseluruhan, studi ini menyimpulkan bahwa manajemen sekolah yang secara konsisten menerapkan prinsip-prinsip SRA mampu menciptakan lingkungan belajar yang aman dan mendukung, sehingga berkontribusi secara signifikan dalam meningkatkan kesejahteraan psikologis siswa.